2009
DOI: 10.1603/029.102.0511
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Neonicotinoid Insecticides From Coated Seeds to Seedling Guttation Drops: A Novel Way of Intoxication for Bees

Abstract: The death of honey bees, Apis mellifera L., and the consequent colony collapse disorder causes major losses in agriculture and plant pollination worldwide. The phenomenon showed increasing rates in the past years, although its causes are still awaiting a clear answer. Although neonicotinoid systemic insecticides used for seed coating of agricultural crops were suspected as possible reason, studies so far have not shown the existence of unquestionable sources capable of delivering directly intoxicating doses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
207
0
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(238 citation statements)
references
References 14 publications
10
207
0
16
Order By: Relevance
“…Measurements of high residue levels of some intrinsically highly toxic, systemic insecticides in guttation droplets from different crops were reported by different researchers (Girolami et al, 2009; and triggered research activities on the risks for bees in 2009. Studies have since been conducted on the environmental conditions and factors favoring guttation, the occurrence of guttation in different crops, the frequency of guttation events and residue measurements in guttation droplets in different crops with different active ingredients in different growth stages (Pistorius et al, 2011a).…”
Section: Residues In Guttation Dropletsmentioning
confidence: 99%
“…Measurements of high residue levels of some intrinsically highly toxic, systemic insecticides in guttation droplets from different crops were reported by different researchers (Girolami et al, 2009; and triggered research activities on the risks for bees in 2009. Studies have since been conducted on the environmental conditions and factors favoring guttation, the occurrence of guttation in different crops, the frequency of guttation events and residue measurements in guttation droplets in different crops with different active ingredients in different growth stages (Pistorius et al, 2011a).…”
Section: Residues In Guttation Dropletsmentioning
confidence: 99%
“…Observations are done at the level of the colony and only individual observations on bees are included insofar as they may affect colony development. In principle, guttation water would not be a major source of exposure given that normally these droplets occur mainly in early plant developmental stages (Girolami et al, 2009;Tapparo et al, 2012). However, the individual geographical and meteorological conditions of each area should be considered to exclude this potential exposure route.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the sowing of treated maize seed with the use of pneumatic drilling machine pose an additional, considerable routes of pesticide exposure for honey bees. Drift of insecticidal dusts of coated maize seed during sowing results in contamination of the surrounding areas with flowering bee forage plants and may cause high bee mortality (Greatti et al, 2003;Greatti et al, 2006;Bortolotti et al, 2009;Girolami et al, 2009;Pistorius et al, 2009;Marzaro et al, 2011;Georgiadis et al, 2012;Sgolastra et al, 2012). In North America, where at least 94% of the 36 million hectares planted with maize is treated with clothianidin or thiametoxam, those crops are considered a major source of neonicotinoid exposure for bees living near agricultural fields (Krupke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%